Associative recognition memory for faces: more pronounced age-related impairments in binding intra- than inter-item associations - Jäger, Theodor; Mecklinger, Axel; Kliegel, Matthias (Experimental aging research, 2010)
Performance in recognition memory for associations between arbitrarily paired items is substantially disrupted in old age. The present study examined whether older adults show more or less of a deficit when the to-be-associated items can be ‘unitized’ into a single representation during encoding. Results revealed that older adults are disproportionately impaired in their memory for unitizable face-pairs, suggesting substantial age deficits in unitization processes required for the formation of associations between highly overlapping stimuli. Potential compensatory mechanisms are discussed that may account for these preliminary results of a selective age deficit in the encoding or retrieval of intra-item associations.
Gesehen am 11.07.2023